(untitled) (Ciudades, 2017)
This present contribution constitutes a synthesis of the state of the art in the spatial analysis tools available for application to land use, regional and town planning land of relevance to planning experts in the exercise of their professional responsibilities in public administration or in consulting and engineering companies, with particular reference to the Spanish context. Briefly, the basic tools which will be discussed correspond to statistical systems (demographic censuses and market share indicators), cartographic systems and software and Geographic Information Systems (GIS), the specific regulatory systems (environmental, town planning and land use planning regulations) and the use of spatial models (with particular reference to theories of central places and the spatial dissemination of innovations). Lastly, the task of territorial diagnosis will be considered, which should include a definition of the territorial problems to be tackled, an explanation of their possible inter-relationships and the objectives pursued, prior to implementation and management of territorial planning strategies.